Neuroinflammation and Neuroimmune Dysregulation after Acute Hypoxic-Ischemic Injury of Developing Brain - Bhalala, Utpal S.; Koehler, Raymond C.; Kannan, Sujatha (Frontiers in Pediatrics, 2015)
Hypoxic-ischemic injury to developing brain results from birth asphyxia in neonates and from cardiac arrest in infants and children. It is associated with varying degrees of neurologic sequelae, depending upon the severity and length of hypoxia-ischemia. Global hypoxia-ischemia triggers a series of cellular and biochemical pathways that lead to neuronal injury. One of the key cellular pathways of neuronal injury is inflammation. The inflammatory cascade comprises activation and migration of microglia—the so-called “brain macrophages,” infiltration of peripheral macrophages into the brain, and release of cytotoxic, proinflammatory cytokines. In this article, we review the inflammatory and immune mechanisms of secondary neuronal injury after global hypoxic-ischemic injury to developing brain. Specifically, we highlight the current literature on microglial activation in relation to neuronal injury, proinflammatory and anti-inflammatory/restorative pathways, the role of peripheral immune cells, and the potential use of immunomodulators as neuroprotective compounds.